The effect of health professionals’ perceptions of organizational impediments on emotional labor and job satisfaction - Gündüz Çekmecelioğlu, Hülya; Balkaş, Jale; Altaş, Sabiha Sevinç; Sevimli Güler, Döndü (Frontiers in Psychology, 2025)
IntroductionHealthcare professionals are often required to manage their emotions effectively within the workplace, a task that can contribute to considerable stress and psychological strain. Emotional displays, which can be affected by organizational impediments, can affect healthcare workers’ levels of job satisfaction.Materials and methodsThe study adopts a cross-sectional research design. Data were collected from 651 healthcare professionals in Turkey through a convenience sampling method, utilizing online and face-to-face survey questionnaires, and analyzed using SPSS Process Macro v4.2 and AMOS v24.ResultsThe findings reveal that organizational impediments positively impact the surface acting and deep acting, as they compel healthcare workers to invest more effort, planning, and control in managing their emotions. However, these impediments also negatively affect job satisfaction. Furthermore, surface acting and deep acting were found to have distinct effects on job satisfaction, with surface acting serving as a mediator between organizational impediments and reduced job satisfaction.ConclusionThe findings highlight the significant role of surface behaviors in mediating the negative relationship between organizational impediments and job satisfaction, underscoring their critical impact on employee satisfaction. Moreover, the pronounced influence of deep acting on job satisfaction emphasizes the need for strategies aimed at preserving or enhancing employees’ intrinsic motivation. These insights suggest that health institutions should prioritize the development of policies designed to alleviate the emotional labor demands placed on employees. Furthermore, addressing and mitigating organizational impediments appears to be a key strategy for fostering higher levels of job satisfaction among healthcare professionals. These results were compared with findings from previous studies and discussed within the theoretical frameworks of Job Demands-Resources (JD-R) and Conservation of Resources (COR) theories.